2013
DOI: 10.1016/j.ajhg.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Topical Enzyme-Replacement Therapy Restores Transglutaminase 1 Activity and Corrects Architecture of Transglutaminase-1-Deficient Skin Grafts

Abstract: Transglutaminase-1 (TG1)-deficient autosomal-recessive congenital ichthyosis (ARCI) is a rare and severe genetic skin disease caused by mutations in TGM1. It is characterized by collodion babies at birth, dramatically increased transepidermal water loss (TEWL), and lifelong pronounced scaling. The disease has a tremendous burden, including the problem of stigmatization. Currently, no therapy targeting the molecular cause is available, and the therapeutic situation is deplorable. In this study, we developed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 42 publications
(52 reference statements)
1
45
0
5
Order By: Relevance
“…Indeed, at least two clinical trials aiming for transcutaneous vaccine delivery via the hair follicles were initiated or conducted just recently. Moreover, recent studies provided the proof of concept for a local protein substitution therapy which may open a new treatment option for severe skin diseases (Aufenvenne et al, 2013;Stout et al, 2014). These studies, however, are at a very early stage so that further investigations are crucial to allow for conclusions about the practicability of this approach.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, at least two clinical trials aiming for transcutaneous vaccine delivery via the hair follicles were initiated or conducted just recently. Moreover, recent studies provided the proof of concept for a local protein substitution therapy which may open a new treatment option for severe skin diseases (Aufenvenne et al, 2013;Stout et al, 2014). These studies, however, are at a very early stage so that further investigations are crucial to allow for conclusions about the practicability of this approach.…”
Section: Discussionmentioning
confidence: 97%
“…Aufenvenne et al (2013) developed sterically stabilized liposomes, equipped with a cationic lipopeptide, and encapsulated recombinant human transglutaminase 1 (molecular mass 92 kDa) in order to address the underlying cause of autosomal recessive congenital ichthyosis. The unilamellar vesicles were composed of phosphatidylcholine and poly(ethylene glycol)-2000-dipalmitoyl-phosphatidylethanolamine and were about 200 nm in size.…”
Section: Liposomes For Dermal Protein/peptide Deliverymentioning
confidence: 99%
“…Recently, Aufenvenne et al [34] have developed the basis for an enzyme-replacement therapy for individuals suffering from TGase1-deficient ARCI. They demonstrated that a topical approach using a formulation of liposomal-encapsulated recombinant human TGase-1 is suitable for restoring TGase-1 activity in the upper stratified layers of the epidermis to reconstitute epidermal integrity and barrier function in a mouse model.…”
Section: Tgm1mentioning
confidence: 99%
“…All these steps have been realized . A skin humanized mouse model was developed in which human skin equivalents of TG1‐deficient patients were grafted onto athymic nude mice.…”
Section: Inherited Skin Diseases Associated With Tg1 Deficiencymentioning
confidence: 99%